The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/2317-1545v38n2161132
|View full text |Cite
|
Sign up to set email alerts
|

Methods for priming maize seeds

Abstract: -This study aimed to evaluated different methodologies and water potentials for priming of maize seeds, in order to increase vigor. The experiment was carried out following a completely randomized design, in a factorial scheme 4x3+1, with four water potentials (0.0, -0.4, -0.8 and -1.2 MPa), three priming methods (immersion in non-aerated solution, immersion in aerated solution, paper roll) and a control. After priming, the seeds were dried and evaluated for water content, percentage and first germination coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…The first germination count is a test associated with germination but that expresses seed vigor. Pallaoro et al (2016), when studying the effect of physiological priming on corn seeds, also found higher percentages of normal seedlings in the first count, and different from what was observed in this study, the authors also emphasized improvements in the final seed germination percentage.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The first germination count is a test associated with germination but that expresses seed vigor. Pallaoro et al (2016), when studying the effect of physiological priming on corn seeds, also found higher percentages of normal seedlings in the first count, and different from what was observed in this study, the authors also emphasized improvements in the final seed germination percentage.…”
Section: Resultscontrasting
confidence: 99%
“…Sediyama et al (2012) found a reduction in damage and lesions in soybean seeds after the use of osmopriming. Pallaoro et al (2016) also saw this effect when using an osmotic agent in the priming of corn seeds.…”
Section: Resultsmentioning
confidence: 89%
“…Immersion methods cause rapid water uptake compared to solid osmotic media that rehydrates seed slowly. Rapid, uncontrolled imbibition is often associated with more electrolyte leakage since desiccation damaged cell membranes need time to reconstitute (Pallaoro et al, 2016) which could explain the slower rate of germination and related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of priming on low temperature tolerance of maize are frequently limited to an individual hybrid genotype within a study to enable comparisons among priming methods. Multiple studies have compared hydropriming with other priming agents with hydropriming consistently showing less improvement in germination or emergence [ 16 22 ]. Micronutrient or osmotic priming agents can improve germination and early seedling development at sub-optimal temperatures [ 19 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have compared hydropriming with other priming agents with hydropriming consistently showing less improvement in germination or emergence [ 16 22 ]. Micronutrient or osmotic priming agents can improve germination and early seedling development at sub-optimal temperatures [ 19 , 20 , 22 , 23 ]. Some hormones, reducing/oxidizing chemicals, chitosan, and even Moringa oliferia leaf extracts have been shown to increase germination or seedling emergence in low temperatures [ 16 18 , 20 , 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%